ГЕОГРАФИЧЕСКИЕ ТЕРМИНЫ С КОРНЕМ НИЗ- В РУССКОЙ РЕЧИ ПЕРМСКОГО КРАЯ (Филологические заметки, 2019)
The article deals with 30 geographical terms – appellatives with a root низ- (нижина, низбина, низедь, низмедь, низмень etc.) naming a low place on a surface, functioning in dialects and popular speech of the Perm region. Six of them are Russian, the others are dialectal, and only three are fixed in the Perm written monuments of the XVII century. The ethymology of appellatives, the features of their formation, a variety of their suffixes (-ина, -ка, -едь, -ынь) are shown in the text. The special attention is given to the analysis of words in which traces of an ancient suffix of common Slavic language *-men (compare пламень), which originates from the Indo-European parent language (низмень, низменка, низменность), were preserved in words низмедь, низметь, низмедина, низметина, низмина, низмятка.